Ekstrak Etanolik Daun Awar-Awar (Ficus septica Burm F.) secara Sinergis Meningkatkan Efektivitas Doxorubicin terhadap Sel Kanker Payudara T47D - RATIH HARDIKA PRATAMA; YURISTA GILANG IKHTIARSYAH; ANINDYAJATI ANINDYAJATI; ADTYA FITRIASARI; MUTHI IKAWATI; EDY MEIYANTO (Fakultas Farmasi Universitas Pancasila, 2011)
Awar awar leaves which have not been optimally utilized in cancer treatment, are potential to be used in combination with doxorubicin (DOX), an agent used for chemotherapy. The aim of this experiment is to find out cytotoxic effect of awar-awar leaves ethanolic extract (ALE) and its combination with DOX towards breast cancer cells of T47D. ALE was prepared by macerating the dried-leaves powder with ethanol 70%. The cytotoxic effect of ALE toward breast cancer cells was tested employing MTT assay to the treatments both as a single agent and as a combination with doxorubicin (ALE DOX). The cytotoxicity was determined as IC50 value, while effectiveness of combination was measured by combination index (CI) to determine whether the effect is synergic, addictive, or antagonistic. Cytotoxic tests on single treatment ALE for a period of 24 hours resulted to a cytotoxic effect with IC so value of 13 µg/mL. ALE-DOX combination showed synergistic effect (CI < 1) on the concentration of 4.88 µg/mL (ALE) and 3.75 nM (DOX). The results showed that ALE is potential to be used as doxorubicin co-chemotherapeutic agent in breast cancer therapy.